Study of the emotionality of phraseology in general and Turkic linguistics (Journal of Oriental Studies, 2021)
The article studies human emotions in the emotional and linguacultural space, particularly focused on the study of emotional intensity of phraseology. The author considers the concepts of emotional codes, human feelings and ways of expressing them, and analyzes new approaches to the study of emotionality. The main purpose of the article is to describe the diversity of the emotional content of the word and show the importance of studying the emotional code of the language in modern linguistics and linguocultural context based on Turkic languages. Therefore, since the object is an emotional phraseological units, the focus is on the phraseology that comes with the components of ethno-cultural expressive meaning. The article compares and analyzes phraseological units in the Kazakh, Azerbaijani and Turkish languages ​​and their emotional, discursive, pragmatic meaning. The method of comparing emosems in Turkic languages ​​with their equivalents in other languages ​​is also used. As the result of the work were analyzed the emotional words (phraseology) of the Kazakh and Turkic languages ​​and were revealed their place in the speech act and the significance of scrutinizing these elements.Keywords: Kazakh phraseological units, Turkic phraseological units, phraseological units, emotional intensity of phraseological units, emotionality.